Relationship between Factor VIII Mutation Type and Inhibitor Development in a Cohort of Previously Untreated Patients Treated with Recombinant Factor VIII (Recombinate™) - Goodeve, Anne C.; Williams, Ian; Bray, Gordon L.; Peake, Ian R.; for the Recombinate™ PUP Study Group (Thrombosis and Haemostasis, 2000)
A cohort of 79 previously untreated patients (PUPs) with moderatesevere haemophilia A (baseline Factor VIII <2%) were enrolled in a study to evaluate the safety, efficacy and immunogenicity of recombinant factor VIII (r-FVIII, Recombinate™). Blood samples were obtained retrospectively from a total 55 PUPs who were investigated for the spectrum of FVIII gene mutations responsible for their haemophilia. FVIII gene inversion mutations were found in 27 (49%) patients. Two patients had partial gene deletions. The remaining 26 patients were then screened for mutations in the FVIII gene coding region using conformation sensitive gel electrophoresis. Point mutations were identified in 22 (85%) of the patients and 14 of these mutations were novel. Study subjects were monitored for the development of FVIII inhibitors throughout the study. A total of 23 of the 73 evaluable subjects (including one subject with a low inhibitor titer at baseline) demonstrated an inhibitor on one or more occasions; 11 (15%) were persistent. Inhibitors were detected in patients with partial gene deletions and inversions and in three of eight patients with missense mutations. No inhibitors were found in 11 patients with small insertions or deletions resulting in an alteration of the protein translation reading frame (frameshift mutations). The results corroborate the observation that mutation type is an important determinant of the propensity to develop inhibitory anti-FVIII antibody.
Keywords: Haemophilia A; factor VIII gene; inhibitor; mutation; FVIII inversion